Home advantage in European international soccer: Which dimension of distance matters? - Nils van Damme; Stijn Baert (Kiel Institute for the World Economy (IfW), 2019)
The authors investigate whether the home advantage in soccer differs by various dimensions of distance between the (regions of the) home and away teams: geographical distance, climatic differences, cultural distance, and disparities in economic prosperity. To this end, they analyse 2,012 recent matches played in the UEFA Champions League and UEFA Europa League. The authors find that when the home team plays at a higher altitude, they benefit substantially more from their home advantage. Every 100 meters of altitude difference is associated with an increase in expected probability to win the match, as the home team, by 1.1 percentage points.
Keywords: L83; J44; Z00; 330; soccer; home advantage; cultural distance; UEFA Champions League; UEFA Europa League